2020
DOI: 10.3390/foods9091184
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Bacterial Diversity of Human Milk during Late Lactation Period (Weeks 21 to 48)

Abstract: Breast milk from a single mother was collected during a 28-week lactation period. Bacterial diversity was studied by amplicon sequencing analysis of the V3-V4 variable region of the 16S rRNA gene. Firmicutes and Proteobacteria were the main phyla detected in the milk samples, followed by Actinobacteria and Bacteroidetes. The proportion of Firmicutes to Proteobacteria changed considerably depending on the sampling week. A total of 411 genera or higher taxons were detected in the set of samples. Genus Streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(60 reference statements)
2
3
0
Order By: Relevance
“…Firmicutes significantly increased over time while Proteobacteria significantly decreased from week 4 to 24 lactation. This is in line with other studies that have reported that Firmicutes and Proteobacteria dominate in milk samples, but their proportions change considerably depending on sampling week 43 .…”
Section: Discussionsupporting
confidence: 93%
“…Firmicutes significantly increased over time while Proteobacteria significantly decreased from week 4 to 24 lactation. This is in line with other studies that have reported that Firmicutes and Proteobacteria dominate in milk samples, but their proportions change considerably depending on sampling week 43 .…”
Section: Discussionsupporting
confidence: 93%
“…This is probably due to the inclusion of the phylum Proteobacteria , which together with the Bacteroidetes , Firmicutes , and Actinobacteria phyla represents approximately 98% of the bacterial phyla present in human milk. Similar findings have been observed by others [ 36 , 37 , 38 ]. As in the human intestine, the proportions of Firmicutes and Bacteroidetes had higher medians than the phylum Actinobacteria [ 3 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Preparation of Bacterial Cultures and Spore Suspensions for Human Milk Inoculation. Vegetative bacterial strains (Cronobacter sakazakii, 34 Enterococcus faecium, 35 Listeria monocytogenes 36 , and Staphylococcus aureus 37 ) and spore-forming bacteria (Bacillus subtilis, Bacillus cereus, Paenibacillus macerans, and Paenibacillus polymyxa 38 ) were selected for inoculation in this study based on their potential presence in donor human milk and/or the detection of their species or genera in donor human milk as contaminants (Supplementary Table 1). All bacteria were maintained cryogenically by the Food Safety Systems Lab (Oregon State University, Corvallis, OR).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%